(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, a wide range of ideas and facts are presented as the main link of the effectiveness of interactive methods in the course of physical education lessons. Also, detailed recommendations on the effective use of interactive methods in physical education classes are given.